Religion and Management: Redefining God's Kingdom Management for Human Resources Post COVID-19 - Wiryadinata, Halim; Adi, Suwarto; Rumbay, Christar Arstilo; Pathmanathan, Joseph Winston Napoleon (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
This research analyzes the shifting of management of God's Kingdom to focus on saving human resources in the economic site due to COVID-19. The old paradigm of management of God's Kingdom, which is to save human resources biblically, shifts to humans from the low economic condition. This study aims to redefine the shifting of management of God's Kingdom as the form of human resources development from the economic perspective. This study systematically presents the economy's condition due to COVID-19, the Church's response to it, and the redefinition of God's Kingdom management through the descriptive qualitative method. This research confirms the redefinition of management of God's Kingdom as the Church's response to help human resources. Finally, this research aims to give out some charity programs and skill training in saving human resources in responding to the economic downward due to COVID-19.